Influence of Stratigraphic Conditions on the Deformation Characteristics of Oil/Gas Wells Piercing Longwall Pillars and Mining Optimization - Shun Liang; Derek Elsworth; Xuehai Fu; Xuehua Li; Qiangling Yao (Energies, 2017)
Hydrocarbon wells drilled vertically through longwall coal pillars are vulnerable to severe deformation and potential failure as a result of underground coal mining. The lithology of the host rocks play a critical role in well stability. In this study, a two dimensional finite element method is employed to investigate the horizontal shear offset, vertical delamination, and compression at the weak interface between neighboring soft and stiff layers after the sequential extraction of longwall panels flanking the protective coal pillar. The influence of stratigraphic conditions, including the single rock layer thickness (SRLT), seam mining height (SMH), and seam dip angle (SDA), on deformation of hydrocarbon wells is explored. An optimization of mining sequence along strike and for panel advance direction along dip is also performed. Finally, some recommendations regarding coal mining and peripheral support measures are suggested.